An analysis of a translation of a scientific text according to juliane house's model of translation assessment - Fenderico, Giancarlo (My University, 2015)
This translation project attempts to examine the applicability of Juliane House's theory for translation evaluation on a scientific text. To this end, an article on cellular biology taken from a scientific journal (Naturwissenschaften, Vol. 62, pp. 331-340) was translated by the author, and problems of a terminological and syntactic nature were examined. Although terminological and syntactic peculiarities seem to be related, a lot of emphasis was placed on the latter in an attempt to show that style does in fact play a role in the translation of scientific and technical texts. For the sake of clarity, the annotations to the translation were divided into two broad categories: annotations of a stylistic nature and annotations of a terminological nature. Furthermore, the annotations dealing with stylistic and syntactic peculiarities were divided into four subsections: additions, repetitions, syntactic changes and use of the impersonal.